EFFECT OF VEDIYUPPU CHEYANEER IN ETHYLENE GLYCOL INDUCED HYPEROXALURIA MODEL IN RATS: Pharmaceutical Science-Pharmacology - V.VELPANDIAN; S. S.RAJAPREHIDHA; V.BANUMATHI; J. ANBU; ANJANA, ASHWINI (International Journal of Life Science and Pharma Research, 2012)
Vediyuppu cheyaneer has been widely used in Siddha system of medicine for various diseases. The liquid form of Vediyuppu cheyaneer showed a significant inhibitory effect when screened at 500 mg/kg, for the invivo antiurolithiasis activity on ethylene glycol induced hyperoxaluria rats. The standard frusemide (20 mg/kg) and cystone (750 mg /kg) were used as comparison for diuretic and antiurolithiatic activity respectively.